Distance and degree based topological characterization, spectral and energetic properties, and 13C NMR signals of holey nanographene - Savari Prabhu; M. Arulperumjothi; Fikadu Tesgera Tolasa; S. Govardhan (Electrochemistry Communications)
Cycloarenes represent a class of polycyclic aromatic compounds distinguished by their intricate molecular structures, where multiple benzene rings are fused together to form macrocyclic frameworks. These structures enclose cavities, with carbon-hydrogen bonds pointing inward, influenced by the arrangement of benzene units in both angular and linear patterns. The unique geometric and electronic properties of cycloarenes, stemming from their superaromaticity, have garnered significant interest among researchers, leading to the exploration of their magnetic and electrical characteristics. Recently, a breakthrough was achieved with the synthesis of a holey C216 nanographene featuring three strands of benzene rings. This achievement underscores the importance of characterizing the topology of such complex molecules to elucidate their properties accurately. In this study, we investigated holey nanographenes with varying numbers of benzene ring strands, employing calculations to determine topological indices. Additionally, the study evaluated the energetic and spectral properties of these molecules. By providing vital insights into the structural and electrical properties of cycloarenes, these findings have the potential to pave the path for applications across a wide range of scientific areas.